Pediatric Percutaneous Nephrolithotomy Using Adult Sized Instruments: Our Experience - Etemadian, Masoud; Maghsoudi, Robab; Shadpour, Pejman; Mokhtari, Mohammad Reza; Rezaeimehr, Behkam; Shati, Mohsen (Urology Journal, 2012)
PURPOSE: To evaluate the safety and efficacy of pediatric percutaneous nephrolithotomy (PCNL) using adult sized instruments in the management of pediatric urolithiasis. MATERIALS AND METHODS: We retrospectively reviewed the medical records of 38 children younger than 15 years who had undergone 45 PCNLs with adult sized instruments in our center between August 2007 and February 2010. RESULTS: There were 26 boys and 12 girls, with a mean age of 8.4 ± 4.24 years (range, 12 months to 13 years). Twelve patients had complete staghorn stone. Mean stone burden was 2.93 ± 0.89 cm. The tract was dilated between 26 and 30 F. Standard PCNL was performed in 8 patients and tubeless PCNL in the next 37 subjects. Simultaneous transurethral lithotripsy was done in 9 patients. Stone clearance rate was 67%. Mean pre and postoperative hemoglobin levels were 12.67 ± 1.7 and 11.39 ± 1.6 g/dL, respectively. Mean hospitalization was 3.5 ± 1.1 days. Eight subjects had postoperative fever beyond day 1. Blood transfusion was required in only one patient. In one patient (3 years old) with a staghorn stone, hyponatremia and seizure occurred, which were treated consevatively without any adverse sequela. There was a significant difference in hospital stay between tubeless and standard PCNL groups (P < .02). CONCLUSION: We concluded that PCNL using adult sized instruments was relatively safe in children, with a clearance rate of 67%. We suggest prospective randomized studies to compare mini-perc and adult sized instruments use in pediatric PCNL.